Is Provision of Healthcare Sufficient to Ensure Better Access? An Exploration of the Scope for Public-Private Partnership in India - Sabitri Dutta; Kaushik Lahiri (Kerman University of Medical Sciences, 2015)
Background India's economic growth rate in recent years has been fairly impressive. But, it has been consistently failing to make considerable progress in achieving health related Millennium Development Goal (MDG) targets. Lack of coherence between provisions and utilization becomes the face of the problem. Inadequacies in outreach, access and affordability coupled with escalating healthcare costs have aggravated the problem. Here the application of PublicPrivate Partnership (PPP) model seems to have enormous potential to ease the impasse. Methods This paper tries to find the gap between the provisions and access in healthcare. The paper attempts to construct a Health Infrastructure Index (HII) and Health Attainment Index (HAI) for different states of India. Considering the presence of regional variations found in health infrastructure and attainment among the states, two states, viz. Maharashtra (MAH) and West Bengal (WB) have been chosen. Then contributions of health programs like Rashtriya Swasthya Bima Yojana (RSBY), National Rural Telemedicine Network (NRTN) and Fair Price Shops (FPS), all PPP initiatives, have been assessed for both the states by carrying out comprehensive benefit-cost analysis. Results The health infrastructure for population per unit area captures the outreach/delivery issue and the health attainment reveals the true scenario about how far the infrastructure has been accessed by the people; and the gap between the two, as the paper finds, is the root of the problem. The combined effect of RSBY and NRTN will leave both MAH and WB higher benefits in terms of health attainment. The contributions of RSBY and NRTN have been assessed for both the states by carrying out comprehensive benefit-cost analysis. FPS comes up with immense benefits for WB. It is yet to be implemented in MAH. Conclusion The outreach and access problems arising from deficiencies in infrastructure, human resources and financial ability are expected to be well-addressed by the spread of RSBY and NRTN jointly. The FPS mechanism under PPP initiative can be an effective tool in solving affordability problem by reducing the cost of treatment.